The Effectiveness of M-Health Anemia Rematri Application on Knowledge, Attitudes, and Hemoglobin Levels Among Female Adolescents [Accepted] - Angraini, Nandha Fitri Kartika; Mahalia, Lamia Diang; Legawati, Legawati; Migang, Yena Wineini (Health Dynamics, 2026)
Background: Anemia among adolescent girls remains a public health problem affecting academic performance, productivity, and future reproductive health. Low levels of knowledge and negative attitudes toward anemia prevention are important risk factors. The use of digital-based educational media, such as the M-Health Anemia Rematri application, is expected to improve the effectiveness of health education. This study aimed to determine the effect of education delivered through the M-Health Anemia Rematri application on knowledge, attitudes, hemoglobin levels, and anemia status among adolescent girls at MA Muslimat NU. Methods: This study employed a quasi-experimental design with a one-group pretest–posttest design. The sample consisted of 62 adolescent girls selected using simple random sampling based on the inclusion criteria. The intervention involved educational delivery through the M-Health Anemia Rematri application. Data were collected using questionnaires to assess knowledge and attitudes, as well as measurements of hemoglobin levels and anemia status using a digital Hb device. Data were analyzed using univariate and bivariate methods. Normality was assessed using the Kolmogorov–Smirnov test, while hypothesis testing was conducted using the paired sample t-test, Wilcoxon signed-rank test, and McNemar test. Result: This study was conducted on 62 adolescent girls. The statistical analysis showed that the educational intervention using the M-Health Anemia Rematri application had a significant effect on knowledge (p = 0.001), attitudes (p = 0.001), and hemoglobin levels (p = 0.001). Conclusion: Education through the M-Health Anemia Rematri application is effective in improving knowledge, attitudes, and hemoglobin levels among adolescent girls. This application has the potential to serve as an innovative and accessible educational medium for anemia prevention.